Do foreign firms help make local firms greener? Evidence of environmental spillovers in China - Kim, Nahyun; Sun, Junxiu; Yin, Haitao; Moon, Jon Jungbien (Journal of International Business Studies, 2022)
The literature on foreign direct investment offers rich evidence that foreign firms outperform their local peers in emerging economies from an environmental perspective. However, it remains unclear whether local firms can learn from the environmental excellence of foreign firms to undertake cleaner production, which helps protect the host country’s natural environment. This environmental spillover effect may offer critical support to the pollution halo effect; however, it has received insufficient empirical attention. By analyzing firm-level panel data on environmental performance in China and augmenting them with data from the input–output table, we investigate whether and how foreign firms improve local firms’ environmental management. Our findings present evidence that the presence of foreign firms in the same industry in the same city lowers the pollutant emission intensity of local firms, corroborating the environmental spillover effect. We also discuss two mechanisms for this spillover: community- and industry-based institutional channels. Furthermore, we find that environmental spillovers are stronger among small and medium-sized enterprises and in areas with higher levels of existing pollution.